Corrosion characteristics of zinc–zirconium alloy in c‐SBF and its biocompatibility in vitro/in vivo. Issue 2 (27th August 2019) - Guo, Pushan; Bagheri, Robabeh; Ren, Tiantian; Yang, Lijing; Xu, Cheng; Lin, Jiajia; Liu, Huinan; Sun, Wensheng; Song, Zhenlun
Abstract: Zinc‐based metals have attracted attention as biodegradable implant materials for medical applications. New alloying systems are still being tried. In this study, three kinds of extruded zinc–zirconium alloys (R1, R2, and R3) were prepared, and two of the most important performance of corrosion characteristics and biocompatibility in vitro/in vivo were carefully examined. We found that zirconium content did not linearly influence the corrosion behavior. Zirconium improved the zinc–zirconium alloy corrosion potential, but the strengthening effect was weakened due to the ZrZn 22 phase, leading to microgalvanic corrosion. The alloy with zirconium content of 0.8% (R2) showed high corrosion resistance and minimum initial corrosion rate in the corrected simulated body fluid. R2 alloy also exhibited favorable cytocompatibility and biological histocompatibility. Abstract : Three kinds of extruded zinc–zirconium alloys (R1, R2, and R3) were prepared, and two of the most important performance of corrosion characteristics and biocompatibility in vitro/in vivo were carefully examined. The alloy with zirconium content of 0.8% (R2) showed high corrosion resistance and minimum initial corrosion rate in the corrected simulated body fluid.